ENHANCING MENDELIAN GENETICS CONCEPTS USING A GUIDED COMPUTER-MEDIATED INQUIRY - (:unkn) unknown (SCI METHODICAL CTR-SCI EDUCOLOGICA, 2011)
The purpose of this study was to situate prospective secondary science teachers in an authentic scientific investigation, that of hypothesis testing of inheritance patterns of cats, and then to examine prospective teachers' developing understandings of basic Mendelian genetics, scientific inquiry, and their perceptions of the learning environment. The context of the study was a teaching and learning course focused on inquiry and technology. Data obtained from the twelve participants included: a) pre-post tests of Mendelian genetics concepts; b) videotaped class presentations; c) inquiry project reports; d) audio taped semi-structured interviews; and e) classroom discussions and observations. The findings suggest that engagement in hypothesis testing, within a socio-constructivist framework; can be used to support the integrated acquisition of conceptual knowledge in science. After the module, there was clear evidence that inquiry-based instruction, enriched with computer simulation and collaboration, promoted students' conceptual understanding of Mendelian genetics and understandings of scientific inquiry.
Keywords: hypothesis testing; inquiry-based teaching; learning genetics; modeling in science; EXPLANATORY MODELS; STUDENTS; TECHNOLOGY; SCIENCE